Prevalence of Post-Traumatic Stress Disorder Among Internally Displaced and Undisplaced Children of Khyber Pakhtukhwa (Medical Forum Monthly, 2024)
Objective: War against terror shattered all faculties of living in Khyber Pakhtukhwa. The present study was aimed to explore the prevalence of post-traumatic stress disorder (PTSD) among internally displaced and undisplaced children as these children are our true future and treatment or intervention facilities available for them.Study Design: Observational / descriptive study.Place and Duration of study: This study was conducted at the Department of Physiology, University of Peshawar in 2011.Materials and Methods: IDP children were assessed at schools for internally displaced children at Jalozi Camp whereas undisplaced children were assessed at different schools in Peshawar. Independent sample t-test and chi square were used to assess the prevalence and intensity of PTSD among internally displaced and undisplaced children. Semi structured interview and Post Traumatic Stress Disorder, Child and Adolescent Questionnaire (PTSD CAQ) were used to assess the prevalence and intensity of PTSD.Results: The results supported the hypothesis. It was found that traumatic experiences of war and displacement caused serious psychological problems in children. Internally displaced children reported high levels of PTSD than undisplaced children also internally displaced children scored high on all the three subscales of PTSD CAQ that shows the severity of their reaction to war trauma.Conclusion: It was concluded that children who were exposed to the trauma of war and who faced the uncertain situation of displacement suffered more from PTSD than those who were not displaced from the secure environment of their homes. This study also found that there was no treatment or intervention plan for the psychological treatment of these children.Key Words: War, Posttraumatic Stress Disorder, Children, Internally Displaced And Undisplaced